Growth and biometric relationships of the silver or gold-lip pearl oyster, Pinctada maxima (Jameson, 1901) under land-based culture system - Rao, G Syda; Pattnaik, Phalguni; Biswajit, Dash (Indian Journal of Fisheries, 2016)
The spat of silver or gold-lip pearl oyster, Pinctada maxima (Jameson, 1901), collected from the hulls of mechanized fishing trawlers operating from Visakhapatnam were grown under land-based culture system. The pearl oysters were continuously fed with a mixed diet of micro-algae through a specially designed drip system. The growth in terms of dorsoventral measurement (DVM), weight and thickness as well as the biometric relationships are presented. A maximum DVM of 141 mm and a maximum weight of 292 g were obtained in two years. The land-based culture technology originally developed and patented in India for Pinctada fucata, is also discussed with respect to suitability for culture of P. maxima.